EFFECT OF EXTERNAL FACTORS ON STOCK PRICE - Bayu Aga Wardana; Irma Christiana (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine and analyze the effect of inflation rate, SBI interest rate, money supply and rupiah exchange rate on stock prices in banking companies listed on the LQ 45 index either partially or simultaneously. The approach used in this study is an associative approach. The population in this study were all banking companies registered with the LQ 45 index, while the sample that met the criteria for sampling was observed for six years and as many as five banks registered with the LQ 45 index. Data collection techniques in this study used documentation techniques. The data analysis technique in this study uses the Classical Assumption Test, Multiple Regression, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistical Package for the Social Sciences) software program version 24.00. The results of this study prove that partially the inflation rate, SBI interest rate, money supply and the rupiah exchange rate have no and no significant effect on stock prices, and simultaneously the inflation rate, SBI interest rate, money supply and the rupiah exchange rate have no effect and not significant to stock prices in banking companies listed LQ 45 index